If $m$ times the $m^{th}$ term of an AP is equal to $n$ times its $n^{th}$ term. find the $( m+n)^{th}$ term of the AP.


Given: If $m$ times the $m^{th}$ term of an AP is equal to $n$ times its $n^{th}$ term.

To do: To find the $( m+n)^{th}$ term of the AP.

Solution:

As given,

$n^{th}$ term of AP $=t_n=a+(n−1)d$

$m^{th}$ term of AP $=t_m=a+(m−1)d$

$\Rightarrow mt_m=nt_n$
$\Rightarrow m[a+(m−1)d]=n[a+(n−1)d]$

$\Rightarrow m[a+(m−1)d]−n[a+(n−1)d]=0$

$\Rightarrow a(m−n)+d[(m+n)(m−n)−(m−n)]=0$

$\Rightarrow (m−n)[a+d((m+n)−1)]=0$

$\Rightarrow a+[(m+n)−1]d=0$

But $t_{m+n}=a+[(m+n)−1]d$

$\therefore t_{m+n}=0$

Updated on: 10-Oct-2022

64 Views

Kickstart Your Career

Get certified by completing the course

Get Started
Advertisements